2018
DOI: 10.1186/s12913-018-3735-0
|View full text |Cite
|
Sign up to set email alerts
|

Results from a proactive follow-up intervention to improve linkage and retention among people living with HIV in Uganda: a pre-/post- study

Abstract: BackgroundDespite gains in HIV testing and treatment access in sub-Saharan Africa, patient attrition from care remains a problem. Evidence is needed of real-world implementation of low-cost, scalable, and sustainable solutions to reduce attrition. We hypothesized that more proactive patient follow-up and enhanced counseling by health facilities would improve patient linkage and retention.MethodsAt 20 health facilities in Central Uganda, we implemented a quality of care improvement intervention package that inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(47 citation statements)
references
References 24 publications
1
46
0
Order By: Relevance
“…**Trial also reported in "Target population: all PLHIV prescribed ART" [57] For PLHIV initiated on ART but have disengaged from care, providing cash incentives shows distinct promise in improving retention in HIV care, for perinatal women living with HIV and those who are food insecure [83 •• , 84 •• ]. Amounts needed to make a difference are likely to be small, covering transport costs of getting to clinics and possibly making a minimal contribution to basic food items [81]. Tracing those LTFU is widely practised in African countries, but the evidence we found suggests this should be performed in a targeted way, prioritising those who can be seen face-to-face by a peer worker who has been trained to be encouraging and use problem-solving approaches [81, 82 •• ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…**Trial also reported in "Target population: all PLHIV prescribed ART" [57] For PLHIV initiated on ART but have disengaged from care, providing cash incentives shows distinct promise in improving retention in HIV care, for perinatal women living with HIV and those who are food insecure [83 •• , 84 •• ]. Amounts needed to make a difference are likely to be small, covering transport costs of getting to clinics and possibly making a minimal contribution to basic food items [81]. Tracing those LTFU is widely practised in African countries, but the evidence we found suggests this should be performed in a targeted way, prioritising those who can be seen face-to-face by a peer worker who has been trained to be encouraging and use problem-solving approaches [81, 82 •• ].…”
Section: Discussionmentioning
confidence: 99%
“…Amounts needed to make a difference are likely to be small, covering transport costs of getting to clinics and possibly making a minimal contribution to basic food items [ 81 ]. Tracing those LTFU is widely practised in African countries, but the evidence we found suggests this should be performed in a targeted way, prioritising those who can be seen face-to-face by a peer worker who has been trained to be encouraging and use problem-solving approaches [ 81 , 82 •• ]. Current evidence is lacking on cost-effectiveness of comprehensive health systems strengthening interventions to improve retention in care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that did not measure adherence as an outcome were excluded from the systematic review. Thirty-one journal articles met the inclusion criteria [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] and were included in the systematic review. Figure 1 shows the flowchart of the systematic review process.…”
Section: Resultsmentioning
confidence: 99%
“…HIV outreach is an important service linking facilities and communities. This study did not define outreach precisely, but it is likely to include bringing HIV testing services to populations that do not regularly seek care at facilities, particularly men and adolescents [37], as well as providing adherence counseling, defaulter tracing, and other efforts that have been demonstrated as successful in improving retention in care [38, 39].…”
Section: Discussionmentioning
confidence: 99%